Improving Bendability of Al-Mg-Si Alloy Sheet by Minor Alloying Element Addition - Das, Sazol; Heyen, Matthew; Kamat, Rajeev; Hamerton, Richard (Light Metals 2018, 2018)
AA6XXX series Al–Mg–Si alloys are increasingly being used for outer applications in vehicles due to their good combination of strength and formability. Successful use of aluminum in such applications depends on a very clear understanding of the underlying physical metallurgy gained by studying the formability and its relationship with microstructure in greater detail. For example, the effect of dispersoids formed during the homogenization cycle on bendability is important. In general, lower temperature and longer homogenization time is more effective to produce a large number of dispersoids, whereas higher temperature homogenization tends to coarsen the dispersoids. A large number density of dispersoids improves the material’s bendability, even with a higher Fe content, believed to be due to promotion of more diffuse slip resulting in reduced strain localization and crack blunting. Increase in Mn and Cr also encourages transformation of AlFeSi as-cast constituents (plate-like) to Al(Fe,Mn/Cr)Si (more spheroidal) constituents during homogenization. Spheroidal constituent particles are less likely to initiate cracks in materials subject to deformation and thus help to improve bendability.